Immediate implants in extraction sockets with periapical lesions: an illustrated review - Arthur B. Novaes Jr; Valdir A. Muglia; Umberto D. Ramos; Danilo M. Reino; Lauro G. Ayub (Ariesdue, 2013)
Aim Immediate implantation has gained great attention since first proposed. Immediate implants in replacement of teeth with periapical lesion is, to date, an issue of discussion. The aim of this study is to perform an illustrated literature review of immediate implants in sockets exhibiting previous periapical lesions.Materials and methods A search on medline/EMBASE database was done for the literature review which is presented together with two case reports illustrating the state of the art of immediate implants on sockets with periapical lesions. Both cases are presented in areas with great aesthetic demands and a periapical lesion of considerable size. The two cases were conducted following strict granulation tissue removal and careful rinsing and pre-operative antibiotics, followed by good primary stability of the dental implant.Results and conclusion Both cases represented successes in aesthetics and function, describing a successful protocol for immediate implant installation in areas exhibiting periapical lesions.